2002
DOI: 10.1016/s1010-7940(02)00276-2
|View full text |Cite
|
Sign up to set email alerts
|

Open heart surgery for posttraumatic inferior vena caval thrombosis

Abstract: A 40-year-old woman was diagnosed as intrahepatic hematoma after blunt abdominal trauma. One month later computed tomography (CT) revealed the inferior vena caval thrombus extending into the right atrium. Emergency thrombectomy was performed under cardiopulmonary bypass. We believe that the thrombus, which was derived from laceration of the hepatic vein, extended through the inferior vena cava into the right atrium, and was the eve of pulmonary embolization. CT study should be repeated, once the intrahepatic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…[2][3][4][5] The pathogenesis difficult to go on to remove the thrombus located in the retrohepatic IVC because venous return during the thrombectomy gradually increased and became uncontrollable. We needed a bloodless surgical field to adequately remove the thrombus in the retrohepatic IVC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5] The pathogenesis difficult to go on to remove the thrombus located in the retrohepatic IVC because venous return during the thrombectomy gradually increased and became uncontrollable. We needed a bloodless surgical field to adequately remove the thrombus in the retrohepatic IVC.…”
Section: Discussionmentioning
confidence: 99%
“…Fujii, et al reported thrombectomy of the right atrium, IVC, and middle hepatic vein, which was performed according to the following protocol: 2 minutes of circulatory arrest and 4 minutes of reperfusion at 28°C. 5) Ushijima, et al reported the removal of an organized thrombus from the IVC during 41 minutes of circulatory arrest under deep hypothermia (20°C) without neurological deficit. 8) In our case, we utilized a 5-minute total circulatory arrest at a systemic temperature of 25°C in order to minimize the risk of ischemic cerebrospinal complications and coagulopathy.…”
Section: Fig 3 Intraoperative Photograph (A) the Overall Picture Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…IVCT after blunt trauma is extremely rare, with only a few cases reported in the Englishlanguage literature. [1][2][3][4][5][6][7][8] All cases were reports of acute or subacute thromboembolism. This is the fi rst reported case of surgical treatment for chronic IVCT following blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Only few cases of post traumatic inferior vena cava (IVC) thrombosis have been reported so far in the literature [2], which suggest diagnosis and management difficulties. The major risk of this condition is pulmonary embolism [3]. We report a case of post traumatic IVC thrombosis following closed hepatic injury, diagnosed accidentally on admission, rapidly complicated by pulmonary embolism and managed only by anticoagulation.…”
Section: Introductionmentioning
confidence: 97%